is the equation a true statement when x equals -3 in other words is -3 a solution to the equation 6 x + 5 = 5x +8 + 2x explained ? explain
2 answers:
Answer: Yes
Step-by-step explanation: bc 6(-3)+5=5(-3)+8+2(-3)
Becomes -18+5=-15+8+-6 which equals -13 on both sides meaning -3 is a solution
6x+5=5x+8+2x
6x+5=(5x+2x)+(8)(Combine Like Terms)
6x+5=7x+8
6x+5=7x+8
Step 2: Subtract 7x from both sides.
6x+5−7x=7x+8−7x
−x+5=8
Step 3: Subtract 5 from both sides.
−x+5−5=8−5
−x=3
Step 4: Divide both sides by -1.
−x
−1
=
3
−1
x=−3
Answer:
x=−3
You might be interested in
s hard and too long I'm only of class 13
3 + 3 + 3 = 9 Prime Factorization. 3 x 3
The giant jar of jelly beans is 5 times the size of the smaller jar. If there are 83 jelly beans in the smaller jar, the giant jar can be represented as 5(83).
5(83) = 415 jelly beans
Answer:
They have the same vertical shift. -Apex
Step-by-step explanation:
Ok sorry but there is no picture :(